Effect of processing variables on characteristics of steam-flaked corn - Sindt, J.J.; Montgomery, Sean P.; Loe, E.R.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated tempering moisture concentration, addition of a surfactant to improve moisture uptake, steam conditioning time, and flake density to determine their impact on characteristics of steam-flaked corn. Increasing steam conditioning time from 20 to 40 minutes or adding a surfactant during tempering did not increase final flake moisture concentration, but moisture content of flaked corn was linearly increased by increasing tempering moisture concentration. Addition of Grain Prep® surfactant during tempering decreased (P<0.05) the amount of moisture lost during flaking. Flake durability was increased by increasing tempering moisture concentration, but only if corn was steamed for 40 minutes (tempering moisture × steam time interaction; P<0.10). Decreasing flake density linearly increased both starch availability (P<0.01) and flake durability (P<0.05). In this experiment, tempering moisture concentration had the largest impact on flake moisture content, and flake density was the most influential variable altering flake durability and starch availability.
Keywords: Beef; Steam-flaked corn; Moisture concentration